The Effect of Good Corporate Governance on Financial Performance Mediated by Earnings Management - Shalsya Dian Aprilyana; Rida Perwita Sari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the impact of Good Corporate Governance on financial performance, considering the role of earnings management as a mediating variable. Good Corporate Governance works to increase transparency and accountability, and reduce information asymmetry, both of which can impact a company's financial performance. This research is expected to add to the literature on the relationship between Good Corporate Governance, earnings management, and financial performance. Quantitative research methods are used in this study. The data used in this study are secondary data taken from the company's annual financial statements. The analytical tool used in this research is Partial Least Squares (PLS). The population in this study is a State-Owned Enterprise company listed on the Indonesian Stock Exchange from 2020 to 2023. The results of this study indicate that Good Corporate Governance affects Financial Performance, but it does not affect earnings management. Conversely, Earnings Management affects Financial Performance, and it does not mediate the effect of Good Corporate Governance on Financial Performance.